MUSICAL COLLECTIONS IN PUBLIC AND INSTITUTIONAL COLLECTION MANAGEMENT POLICIES - Castagna, Paulo [UNESP] (Programa Pos-graduacao Musica-ppgm, 2022)
This work addresses the representativeness of musical collections or collections of musical interest in public and institutional collections management policies, based on federal legislation, institutional documents, and bibliographic works on this subject, with the objective of identifying the aspects that benefit or not music-related files and collections. Based on the observation that most of the collections of musical interest are not yet covered by such policies and that the specificities of this type of collection do not always allow the automatic application of criteria specific to other categories of collections, such as archives (especially administrative archives), bibliographic and museological collections, it is concluded that the priority, at the moment, is the development of projects related to the treatment of various types of musical collections, for the development of a culture of preservation of the musical heritage and increase of the social conscience about the historical and cultural importance of musical items in collections of all kinds.
Keywords: Musical Collections; Collection management; Public policy; Institutional policies